2013
DOI: 10.1186/1472-6882-13-178
|View full text |Cite
|
Sign up to set email alerts
|

Red yeast rice lowers cholesterol in physicians - a double blind, placebo controlled randomized trial

Abstract: BackgroundIn recent years, red yeast rice (RYR) supplements have been marketed aggressively as a natural way to lower cholesterol; however, the large majority of commercially available products have not been studied according to current research standards.MethodsIn a double blind placebo controlled randomized trial, 52 physicians and their spouses with a total cholesterol level of > 200 mg/dL were randomly allocated to receive a RYR extract or placebo for 8 weeks. As a primary outcome measure, we compared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 29 publications
(31 reference statements)
1
32
0
Order By: Relevance
“…The RAC contains monacolin K that is an inhibitor of cholesterol synthesis key-enzyme [38, 39]. The RAC formula also contains vitamin E and ubiquinol (vitamin Q), both working in the human body as powerful antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…The RAC contains monacolin K that is an inhibitor of cholesterol synthesis key-enzyme [38, 39]. The RAC formula also contains vitamin E and ubiquinol (vitamin Q), both working in the human body as powerful antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…37 LDL was reduced by 22.17% in the subjects in the red yeast rice arm (P < 0.001) of the study, with a formulation equivalent to 10 mg of daily monacolin K.…”
Section: Red Yeast Ricementioning
confidence: 97%
“…In another experimental study on a rat model of hyperlipidemia, red yeast rice has been found to regulate the balance between blood coagulation and anticoagulation factors, thereby preventing the formation of thrombus and reducing the occurrence of atherosclerosis (Lee, Shih et al 2013) A study aimed at disclosing the mechanism of action of red yeast rice, based on a nonalcoholic fatty liver disease mouse model, has suggested that the therapeutic effect of the product would be independent of monacolin K levels, whereas it should be rather ascribed to GABA and various peptides produced during rice fermentation (Fujimoto, Tsuneyama et al 2012). Conversely, doubleblind clinical studies on hypercholesterolemic subjects have shown that dietary monacolin K is able to reduce cholesterolemia (Cicero, Derosa et al 2013;Verhoeven, Lopez Hartmann et al 2013). …”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%